Dialog Antaragama Sudah Usang: Radical Hospitality dan Masa Depan Relasi Lintas Iman - Adi, Raden Bima (Sekolah Tinggi Teologi Simpson Ungaran, 2025)
Interreligious dialogue is a key mechanism for fostering peace and overcoming religious prejudices. However, in the context of the shift of the 21st century, traditional dialogue models seem increasingly inadequate. This study aims to examine the limitations of conventional interfaith dialogue and explore more relevant alternatives to contemporary interfaith relationships. Conducted in the context of rising interfaith tensions and the influence of digital on belief systems, this study uses a qualitative-critical design by analyzing interfaith literature and contemporary case studies. The findings suggest that passive tolerance and formal exchange no longer meet today's challenges. Instead, the study highlights the urgent need for transformation towards interfaith solidarity, radical friendliness, and joint action for social justice. He concluded that while interfaith dialogue remains important, its form needs to be significantly rethought. The study advocates a transition from outdated frameworks to embrace context-sensitive, critically informed, and transformative methodologies. By introducing practical and forward-looking solutions rooted in urgent social imperatives and scientific rigor, the research advances the discourse on interreligious engagement, bridging the gap between theoretical reflection and urgent collective action.